Pengaruh Penerapan Standar Akuntansi Pemerintahan Berbasis Akrual & Sistem Pengendalian Internal Pemerintah Terhadap Kualitas Laporan Keuangan SKPD Di Pemerintah Kota - Surbakti, RA Sasqia Maharani; Silviana, Silviana (CV. ITTC INDONESIA, 2024)
Management of state finances is carried out on an ongoing basis to ensure orderliness, efficiency, effectiveness, transparency and accountability, as well as meeting demands for public accountability and submission of financial reports in accordance with regulations. Regional Governments are obliged to submit Regional Government Financial Reports (LKPD) as a form of transparency and accountability, which are assessed for credibility by the Financial Audit Agency of the Republic of Indonesia, with the quality of financial reports that are relevant, reliable, comparable and can be understood as a measure of good regional financial management. This research aims to test and analyze whether the quality of implementing Government Accounting Standards (SAP) and the Government Internal Control System (SPIP) has an effect on the quality of financial reports. This research uses an explanatory research method to understand known phenomena, with descriptive verification research to test causal relationships between variables through hypothesis testing. The implementation of Government Accounting Standards and the Government Internal Control System has a positive and significant effect on the quality of the Bandung City Government's financial reports partially, in accordance with the proposed hypothesis. The findings of this research are in line with previous research, which shows that good implementation of SAP and SPI improves the quality of local government financial reports